Family planning practices and pregnancy intentions among HIV-positive and HIV-negative postpartum women in Swaziland: a cross sectional survey - Warren, Charlotte E (BioMed Central, 2013)
BACKGROUND: In settings where sexually transmitted infection (STI) and HIV prevalence is high, the postpartum period is a time of increased biological susceptibility to pregnancy related sepsis. Enabling women living with HIV to avoid unintended pregnancies during the postpartum period can reduce vertical transmission and maternal mortality associated with HIV infection. We describe family planning (FP) practices and fertility desires of HIV-positive and HIV-negative postpartum women in Swaziland. METHODS: Data are drawn from a baseline survey of a four-year multi country prospective cohort study under the Integra Initiative, which is measuring the benefits and costs of providing integrated HIV and sexual and reproductive health (SRH) services in Kenya and Swaziland. We compare data from 386 HIV-positive women and 483 HIV-negative women recruited in Swaziland between February and August 2010. Data was collected on hand-held personal digital assistants (PDAs) covering fertility desires, mistimed or unwanted pregnancies and contraceptive use prior to their most recent pregnancy. Data were analysed using Stata 10.0. Descriptive statistics were conducted using the chi square test for categorical variables. Measures of effect were assessed using multivariate fixed effects logistic regression model accounting for clustering at facility level and the results are presented as adjusted odds ratios. RESULTS: Majority (69.2%) of postpartum women reported that their most recent pregnancy was unintended with no differences between HIV-positive and HIV-negative women: OR: 0.96 (95% CI) (0.70, 1.32). Although, there were significant differences between HIV-positive and HIV-negative women who reported that their previous pregnancy was unwanted, (20.7% vs. 13.5%, p = 0.004), when adjusted this was not significant OR: 1.43 (0.92, 1.91). 47.2% of HIV-positive women said it was mistimed compared to 52.5%, OR: 0.79 (0.59, 1.06). 37.9% of all women said they do not want another child. Younger women were more likely to have unwanted pregnancies: OR: 1.12 (1.07, 1.12), while they were less likely to have mistimed births; OR: 0.82 (0.70, 0.97). Those with tertiary education were less likely to have unwanted or mistimed pregnancies OR: 0.30 (0.11, 0.86). Half of HIV-positive women and more than a third of HIV-negative women reported that they had been using a FP method when they became pregnant with no differences between the groups: OR: 1.61 (0.82,3.41). Only short-acting methods were available to these women before the most recent pregnancy; and available during the postpartum visit. One fifth of all women received an FP method during the current visit. Among the four fifths who did not receive a method 17.3% reported they were already using a method or were breastfeeding. HIV-positive women were more likely to have already started a method than HIV-negative women (20% vs. 15%, p = 0.089). CONCLUSION: There are few differences overall between the experiences of both HIV-positive and negative women in terms of FP experiences, unintended pregnancy and services received during the early postpartum period in Swaziland. Women attending postpartum facilities are receiving satisfactory care. Access to a wider range of effective methods is urgently needed if high levels of unintended pregnancy are to be reduced among HIV-positive and HIV-negative women living in Swaziland.